Les Dommages Punitifs En Droit Québécois: Tradition, Évolution Et… Révolution ? - Samson, Mélanie (Revue de droit de l'Université de Sherbrooke, 2012)
Under the common law, it is widely accepted that punitive damages may be awarded in situations where a defendant’s conduct has been malicious, oppressive or abusive. An award of exemplary damages seeks to punish the defendant, acts as a deterrent to the defendant and to others from acting in this manner and expresses the outrage of the court regarding the defendant’s behavior. On the contrary, under Quebec law, the awarding of punitive damages remains exceptional in nature.